The Epitaph of Julius Terentius - Welles, C. B. (Harvard theological review, 1941)
Investigation of the Agora area at Dura was begun in 1931, and continued in the following seasons of work. It is now possible to trace in some detail the history of the site, which developed from an open square only partly enclosed by simple market buildings into a complex of public and private structures. From one of the latter, a private house built in the late second century in the northwest part of the area (G5 H), came the inscription which is the subject of the present paper.